Morbillivirus Receptors and Tropism: Multiple Pathways for Infection - Sato, Hiroki; Yoneda, Misako; Honda, Tomoyuki; Kai, Chieko (Frontiers in Microbiology, 2012)
Morbilliviruses, which include measles virus (MeV), canine distemper virus, and rinderpest virus, are among the most important pathogens in their respective hosts and cause severe syndromes. Morbilliviruses are enveloped viruses with 2 envelope proteins, one of which is hemagglutinin (H) protein, which plays a role in binding to cellular receptors. During morbillivirus infection, the virus initially targets lymphoid cells and replicates efficiently in the lymph nodes. The principal cellular receptor for morbillivirus is signaling lymphocyte activation molecule (SLAM, also called CD150), which is exclusively expressed on immune cells. This feature reflects the strong lymphoid cell tropism and viral spread in the infected body. Morbillivirus infection, however, affects various tissues in the body, including the lung, kidney, gastrointestinal tract, vascular endothelium, and brain. Thus, other receptors for morbilliviruses in addition to SLAM might exist. Recently, nectin-4 has been identified as a novel epithelial cell receptor for MeV. The expression of nectin-4 is localized to polarized epithelial cells, and this localization supports the notion of cell tropism since MeV also grows well in the epithelial cells of the respiratory tract. Although 2 major receptors for lymphoid and epithelial cells in natural infection have been identified, morbillivirus can still infect many other types of cells with low infectivity, suggesting the existence of inefficient but ubiquitously expressed receptors. We have identified other molecules that are implicated in morbillivirus infection of SLAM-negative cells by alternative mechanisms. These findings indicate that morbillivirus utilizes multiple pathways for establishment of infection. These studies will advance our understanding of morbillivirus tropism and pathogenesis.